Constructing the representation by analogy in the process of understanding oral scientific speech - Lebedinskii, Sergey I. (Journal of the Belarusian State University. Philology, 2019)
The basic strategies of sense formation when perceiving oral scientific speech are the strategies of mental representation formation through the transformation (detalization) of schemes, conceptual structures constructing, representations by analogy with known structures or situations, arguments and conclusions focused on the nomination of semantic predictions and its examination. This article experimentally investigates the strategies of constructing the representations by analogy and mechanisms of their execution. It is established that conclusions by analogy are not always reliable, but it is impossible to reach understanding without them. They play an important role in understanding of scientific speech, as they are involved in the formation of hypotheses which are then tested by more rigorous methods, including detailed elaboration and generalization. All revealed and described 12 types of optometery and corrective analogies used by the learners in the process of processing scientific information.